A Rare Encounter with an Expanding Pseudocyst of the Spleen - Ashish Lal Shrestha; Pradita Shrestha (Case Reports in Gastrointestinal Medicine)
Background. Splenic Pseudocyst (SP) is a diagnostic rarity, with cystic lesions of spleen themselves being uncommon. Establishing a preoperative diagnosis could help in specific management but this is rather challenging. Here we present a common presentation of an uncommon diagnosis. Case Presentation. A 47-year-old lady, previously well, presented to the outpatient clinic with intermittent left hypochondrial pain radiating towards left shoulder for 2 months not associated with fever, jaundice, or weight loss. Abdominal examination revealed nontender hepatosplenomegaly. The initial abdominal ultrasonogram (USG) was suggestive of a hydatid cyst, for which she received a course of antihelminthics. At follow-up, after finding no clinical improvement and radiological worsening, she underwent an exploratory laparotomy. A cyst replacing entire lower pole and a significant portion of splenic hilum was found. Total splenectomy was performed. The specimen was reported to be a SP. Conclusion. SP is a unique entity, usually misdiagnosed as a parasitic lesion and often treated with antihelminthic medicines. The natural course of disease, however, follows a subsequent failure of symptom resolution and radiological worsening that ultimately demands surgical attention. Based on size, location, and intraoperative findings, either total or partial splenectomy is required. The final histopathological report often presents a diagnostic surprise.